Artificial Intelligence and the Transformation of the Nepalese Business Environment - Sthapit, Arhan; Vaidya, Rashesh (Journal of Business and Social Sciences Research, 2025)
Artificial Intelligence (AI) is reshaping global business by enhancing operational efficiency, data-driven decision-making, and customer engagement through automation, machine learning, and advanced analytics. Globally, AI is projected to contribute up to USD 15.7 trillion to the economy by 2030, yet it also presents challenges such as workforce displacement and ethical dilemmas. In Nepal, AI adoption is still emerging, with gradual integration observed in banking, insurance, tourism, and hydropower sectors. Existing studies suggest moderate readiness, hindered by skill shortages, inadequate infrastructure, and regulatory constraints. Notable use cases include AI-powered chatbots in banking and microinsurance innovations promoting financial inclusion in rural areas. Although Nepal’s National AI Policy 2025 outlines promising directions, it lacks concrete implementation strategies. Sustainable AI adoption in Nepal will depend on strategic policy interventions, capacity-building efforts, and robust ethical frameworks. Striking a balance between technological innovation and social responsibility is critical for Nepal’s success in the AI-driven future.